(untitled) (Iranian Journal of Kidney Diseases, 2017)
Psoriasis vulgaris is not frequently seen in patients with renal replacement therapy, especially in patients on peritoneal dialysis. Dialysis also has been reported to improve psoriatic skin lesions with a much higher response rate for peritoneal dialysis than haemodialysis. Conversely, we present a case of a man who developed psoriasis after 16 months of peritoneal dialysis. Discontinuation of icodextrin as a possible factor provoking systemic inflammation had no impact on the course of the disease. In this report, we review the existing studies and counsel caution against optimistic expectations of benefits from dialysis in patients with psoriasis.